Para los ninos : palabras de amor e inspiracion de Su Santidad el Papa Juan Pablo II. - John Paul II, Pope, 1920-2005 (New York : Scholastic Press/Callaway Editions, 2000)
A collection of addresses by His Holiness John Paul II, in which he provides words of inspiration particular to young people to guide them in making life choices.
Accelerated Reader
Keywords: Christian children -- Religious life -- Juvenile literature; Christian life -- Catholic authors -- Juvenile literature; Christian life -- Juvenile literature; Conduct of life -- Juvenile literature